Corrosion resistance of aluminum against acid activation in 1.0 M HCl by symmetrical ball − type zinc phthalocyanine - Najah F. H. Alrasheedi; Ismail Abdulazeez; Shamsuddeen A. Haladu; Mohammed A. Gondal; Khaled M. AlAqad; Salwa J. Kamal; Salha N. Alharthi; Asma M. Elsharif (BMC Chemistry, 2024)
Abstract The inhibition effect of symmetrical Ball − type Zinc Phthalocyanine on Aluminum in 1mol/L hydrochloric acid was analyzed by electrochemical techniques. A novel ball-type zinc phthalocyanine (Zn-Pc) inhibitor has been synthesized and verified utilizing FTIR, nuclear magnetic resonance (1H NMR and 13C NMR), MALDI-TOF MS, and absorption spectroscopy (UV-Vis). In addition, laser-induced breakdown and photoluminescence spectroscopy were employed for additional study. Weight loss technique was employed to investigate the corrosion inhibition effectiveness of the synthesized Zn-Pc on Aluminum in 1mol/L hydrochloric acid at the range of variation temperatures (293–333 K). The inhibition efficiency of Zn-Pc increased with higher concentrations of Zn-Pc and decreased as the temperature increased. Furthermore, Zn-Pc demonstrated outstanding outcomes, achieving 72.9% at a very low inhibitor concentration (0.4 mmol/L) at 298 K. The experimental data for Zn-Pc Aluminum in 1mol/L hydrochloric acid obeys the Langmuir adsorption isotherm. Moreover, the corrosion system’s thermodynamic parameters and activation energy were determined. Quantum chemical calculations applying the (DFT) Density Functional Theory method was conducted and applied in this study. These calculations played a pivotal role in elucidating molecular structures and reactivity patterns. Through DFT, numerous reactivity indicators were computed, providing valuable insights into the chemical behavior of the studied compounds. These indicators, such as frontier molecular orbitals, electron density, and molecular electrostatic potential, were subsequently correlated with experimental data.